Ответ:
Объяснение:
Na2SO3 + H2SO4 = Na2SO4 + SO2↑ + H2O
2Na(+) + SO3(2-) + 2H(+) + SO4(2-) = 2Na(+) + SO4(2-) + SO2↑ + H2O
SO3(2-) + 2H(+) = SO2↑ + H2O
BaS + 2HNO3 = Ba(NO3)2 + H2S↑
Ba(2+) + S(2-) + 2H(+) + 2NO3(-) = Ba(2+) + 2NO3(-) + H2S↑
2H(+) + S(2-) = H2S↑
3K2CO3 + 2H3PO4 =2 K3PO4 + 3CO2↑ +3 H2O
6K(+) + 3CO3(2-)+ 6H(+) + 2PO4(3-) = 6K(+) + 2PO4(3-) + 3CO2↑ + 3H2O
CO3(2-) + 2H(+) = CO2↑ + H2O
Ag2CO3 + 2HCl = 2AgCl ↓+ CO2↑ + H2O
Ag2CO3 + 2H(+) + 2Cl(-) = 2AgCl↓ + CO2↑ + H2O
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Объяснение:
Na2SO3 + H2SO4 = Na2SO4 + SO2↑ + H2O
2Na(+) + SO3(2-) + 2H(+) + SO4(2-) = 2Na(+) + SO4(2-) + SO2↑ + H2O
SO3(2-) + 2H(+) = SO2↑ + H2O
BaS + 2HNO3 = Ba(NO3)2 + H2S↑
Ba(2+) + S(2-) + 2H(+) + 2NO3(-) = Ba(2+) + 2NO3(-) + H2S↑
2H(+) + S(2-) = H2S↑
3K2CO3 + 2H3PO4 =2 K3PO4 + 3CO2↑ +3 H2O
6K(+) + 3CO3(2-)+ 6H(+) + 2PO4(3-) = 6K(+) + 2PO4(3-) + 3CO2↑ + 3H2O
CO3(2-) + 2H(+) = CO2↑ + H2O
Ag2CO3 + 2HCl = 2AgCl ↓+ CO2↑ + H2O
Ag2CO3 + 2H(+) + 2Cl(-) = 2AgCl↓ + CO2↑ + H2O